2023
DOI: 10.3389/fphar.2023.1138499
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic medicines in the treatment of Alzheimer’s disease: Pathophysiological links between AD and glucose metabolism

Abstract: Alzheimer’s Disease (AD) is a global chronic disease in adults with beta-amyloid (Aβ) deposits and hyperphosphorylated tau protein as the pathologic characteristics. Although the exact etiology of AD is still not fully elucidated, aberrant metabolism including insulin signaling and mitochondria dysfunction plays an important role in the development of AD. Binding to insulin receptor substrates, insulin can transport through the blood-brain barrier (BBB), thus mediating insulin signaling pathways to regulate ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 252 publications
0
10
0
Order By: Relevance
“…It was reported that amino acids activate AMPK concurrently with mTOR [ 86 ]. However, another study showed that dapagliflozin enhanced AMPK and reduced mTOR [ 20 ]. This may be attributed to the different animal models, as the current study used AlCl 3 -induced AD, while the other study used a D-galactose Alzheimer’s rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that amino acids activate AMPK concurrently with mTOR [ 86 ]. However, another study showed that dapagliflozin enhanced AMPK and reduced mTOR [ 20 ]. This may be attributed to the different animal models, as the current study used AlCl 3 -induced AD, while the other study used a D-galactose Alzheimer’s rat model.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this SGLT2i beneficial effect on cognition was associated with reduced cerebral OS [ 19 ]. As a result, there is mounting evidence that SGLT2is have neuroprotective potential [ 20 ]. Second, our study highlighted the effect of dapagliflozin on glucose transporters and glycolytic enzymes, which was an additional mechanism to its neuroprotective effect reported before.…”
Section: Introductionmentioning
confidence: 99%
“…[182] Although originally designed to block glucose reabsorption in the kidneys, some SGLT-2 inhibitors, such as empagliflozin, have shown promise in preclinical studies for NDs. [183] Despite their generally low lipophilicity, which makes it challenging for them to cross the BBB, they may still offer neuroprotection through indirect mechanisms such as anti-inflammatory effects. Current studies are actively exploring ways to modify the molecular structure of these drugs, potentially enhancing their ability to penetrate the BBB.…”
Section: Sglt-2 Inhibitors In Ndsmentioning
confidence: 99%
“…These changes were correlated with improvements in cognitive functions, such as the ability to remember and learn, as assessed by the novel object recognition and Morris water maze tests [182] . Although originally designed to block glucose reabsorption in the kidneys, some SGLT‐2 inhibitors, such as empagliflozin, have shown promise in preclinical studies for NDs [183] . Despite their generally low lipophilicity, which makes it challenging for them to cross the BBB, they may still offer neuroprotection through indirect mechanisms such as anti‐inflammatory effects.…”
Section: Sglt‐2 Inhibitors In Ndsmentioning
confidence: 99%
“…Both oxidative stress and inflammation are characteristics of AD, and are known to increase BACE1 expression and activity [37][38][39]. Similarly, there are links between oxidative stress and inflammation with hypoglycaemia [40]. BACE1, due to its role in Aβ generation, has become a potential target as a treatment for AD.…”
Section: Introductionmentioning
confidence: 99%